The technology of microcircuit assembly on flexible polyimide substrate - Plis N. I.; Verbitsky V. G.; Zhora V. D.; Volnistov V. N.; Grunyanskaya V. P.; Sergeyeva N. N. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2010)
The research is devoted to technology of microcircuit assembly on flexible polyimide substrate. It is proved that such microcircuits provide high reliability and have advantage over other IC models when applied in hermetic micro-assemblies in microelectronic devices that operate under high accelerations, shocks and strong radiation.